IMPLEMENTASI ONE STOP SERVICE (OSS) PADA BADAN PELAYANAN PERIZINAN TERPADU (BP2T) KOTA MANADO - MERAY, INRI MONICA PRISCILA (JURNAL ADMINISTRASI PUBLIK, 2014)
Manado as the capital city of North Sulawesi is growing rapidly, therefore it requires cooperation from many parties, not only from government but also from the various elements of community to develop Manado to become better. In practice there are still many issues that need to be addressed, for instance, in obtaining permits still have problems on bureaucracy system where the licenses are still convoluted by several agencies.Manado City Government in this regard as policy maker have a clear commitment to the communities which also included in service where it has been stated in the Manado City Regional Regulation Number 05 Year 2008 Regarding with Organization and Work Integrated Licensing Service Agency and the Manado Major Regulation Number 40 Year 2008 Regarding detail Duties and Functions Integrated Licensing Service Agency Manado.However, in this thesis researcher found Manado City Government policy in terms of obtaining permits as one stop service –‘One Roof One Door’- has not been well implemented that there are still constraints, among others, human resources professionals and policy in the issuance of permits (SOP), by improving this issue then hopefully the future of public service -in this case obtaining the permits by employers and society- will be better and will eventually lead to the prosperity of Manado City Government and Society.